Systems Engineering and DevSecOps: Reviewing the Principles. Issue 2 (6th August 2021) - Turner, Richard
ABSTRACT: As software engineering adopts a more continuous delivery mode for embedded and complex systems, systems engineering must adapt and influence DevSecOps and related practices. In this article, I revisit agile, lean, and DevSecOps principles and comment on their interactions, focusing on those that may increase product and system development, deployment, and evolution risk, and those that increase improvement opportunities through productive engagement across the two disciplines. This material is also available as a Software Engineering Institute Blog Post from 15 March 2021 [https://insights.sei.cmu.edu/blog/comparing-devsec-ops-and-systems-engineering-principles/ .]